2022
DOI: 10.1111/acps.13428
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine and COVID‐19 Vaccination: Effects on blood levels and leukocytes. An observational cohort study

Abstract: Objective To investigate the safety of COVID‐19 vaccination in patients on clozapine as regards plasma clozapine concentration and haematological parameters. Methods We conducted a multicentre observational cohort study from 22 February 2021 to 2 September 2021. Primary outcomes were clinically relevant increase in clozapine blood levels (>100 μg/L increase compared to baseline) and clozapine alert levels (>1000 μg/L). Secondary outcomes were granulocytopenia, leukocyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 48 publications
1
22
0
3
Order By: Relevance
“…Observations from case studies need to be supported or discounted based on findings in larger cohort studies. A report of the effects of SARS-CoV-2 vaccines in 139 patients treated with clozapine found no clinically significant changes in symptoms or hematological parameters, but did support the observation from the present case of an increase in median clozapine level (after second dose) of effect size 0.28 and p=0.003 (Veerman et al, 2022). Larger studies such as this could provide the opportunity to investigate potentially complex interactions that could occur with CYP1A2 activity depending on concurrent exposures, such as the smoking status of patients.…”
Section: A Case Report Exploring the Possibility Of Sars-cov-2 Vaccin...supporting
confidence: 84%
See 1 more Smart Citation
“…Observations from case studies need to be supported or discounted based on findings in larger cohort studies. A report of the effects of SARS-CoV-2 vaccines in 139 patients treated with clozapine found no clinically significant changes in symptoms or hematological parameters, but did support the observation from the present case of an increase in median clozapine level (after second dose) of effect size 0.28 and p=0.003 (Veerman et al, 2022). Larger studies such as this could provide the opportunity to investigate potentially complex interactions that could occur with CYP1A2 activity depending on concurrent exposures, such as the smoking status of patients.…”
Section: A Case Report Exploring the Possibility Of Sars-cov-2 Vaccin...supporting
confidence: 84%
“…However, case reports indicated clozapine levels could rise as much as three-fold during SARS-CoV-2 infection, with an increase in the clozapine:norclozapine ratio (Tio et al, 2021). Dose reduction was recommended for clozapine-treated patients experiencing signs and symptoms consistent with clozapine toxicity (Siskind et al, 2020;Veerman et al, 2022).…”
Section: A Case Report Exploring the Possibility Of Sars-cov-2 Vaccin...mentioning
confidence: 99%
“…We found one (0.8%) and two cases (1.7%) of asymptomatic mild neutropenia after the first and second dose respectively with spontaneous recovery, and all three cases had a history of granulocytopenia. Veerman et al similarly reported a low incidence of mild granulocytopenia (3% and 5%), after the first and second dose of the COVID‐19 vaccinations respectively, without cause for additional monitoring 5 …”
Section: Haematological Variablesa N Pre‐vaccination 1 Week After 1s...mentioning
confidence: 95%
“…Veerman et al similarly reported a low incidence of mild granulocytopenia (3% and 5%), after the first and second dose of the COVID-19 vaccinations respectively, without cause for additional monitoring. 5 The strength of our audit is the inclusion of a baseline FBC and 72 hours post-vaccination monitoring for any adverse effects. We drew blood samples 1 week postvaccination with considerations to the case report described by Thompson et al 4 However, it was possible to have underestimated the incidence and severity of haematological or other adverse events as we only obtained 2 follow-up FBCs and captured adverse events only for 72 hours post-vaccination.…”
mentioning
confidence: 99%
See 1 more Smart Citation